Glycosaminoglycan-based hybrid hydrogel encapsulated with polyelectrolyte complex nanoparticles for endogenous stem cell regulation in central nervous system regeneration. (August 2018) - Jian, Wei-Hong; Wang, Huan-Chih; Kuan, Chen-Hsiang; Chen, Ming-Hong; Wu, Hsi-Chin; Sun, Jui-Sheng; Wang, Tzu-Wei
Abstract: The poor regenerative capability of stem cell transplantation in the central nervous system limits their therapeutic efficacy in brain injuries. The sustained inflammatory response, lack of structural support, and trophic factors deficiency restrain the integration and long-term survival of stem cells. Instead of exogenous stem cell therapy, here we described the synthesis of nanohybrid hydrogel containing sulfated glycosaminoglycan-based polyelectrolyte complex nanoparticles (PCN) to mimic the brain extracellular matrix and control the delivery of stromal-derived factor-1α (SDF-1α) and basic fibroblast factor (bFGF) in response to matrix metalloproteinase (MMP) for recruiting endogenous neural stem cells (NSC) and regulating their cellular fate. Bioactive factors are delivered by electrostatic sequestration on PCN to amplify the signaling of SDF-1α and bFGF to regulate NSC in vitro . In in vivo ischemic stroke model, the factors promoted neurological behavior recovery by enhancing neurogenesis and angiogenesis. These combined strategies may be applied for other tissue regenerations by regulating endogenous progenitors through the delivery of different kinds of glycosaminoglycan-binding molecules. Highlights: Awaken innate regenerative capabilities in brain tissue by biomimicry design. Create appropriate microenvironment to promote body's own regenerating capacity. Enhance endogenous neural stem cells recruitment, survival, and proliferation from subventricular zone (SVZ). Protect and control the release of multiple growth factors by polyelectrolyte complex nanoparticles. Establish photothrombotic ischemia (PTI) model in rat brain and provide therapeutic efficacy for stroke rescue.